Організація системи бюджетування на автотранспортних підприємствах - Реслер, М. В.; Resler, M. V. (Видавництво Львівської політехніки, 2017)
У статті запропоновано заходи щодо моделювання механізму бюджетування, який забезпечить єдність підходів, оцінок, ефективне управління фінансово-господарською діяльністю, мінімізацію витрат, активізацію господарської діяльності, досягнення позитивного фінансового результату та забезпечення платоспроможності на автотранс- портних підприємствах.

The content of budgeting in the enterprise in crisis conditions, it outlines the importance of effective impact on the activities of the enterprise in the face of uncertainty and instability of the economy. Proved that the introduction of budgetary fundamentals targeted to the following tasks: improving financial discipline, optimizing the capital structure, the most effective restructuring of the company. It is noted that huge advantage of budgeting procedures is that in the development budget involved all structural units of the company. In this paper proposed measures to modeling budgeting mechanism that will ensure unity of approaches, assessments, effective management of financial and economic activity, minimizing costs, increased economic activity, a positive financial result and solvency on transport enterprises. Considered types of budgets covering virtually all aspects of business enterprises, whereby it was established that budgeting is a technology integrated economic planning. The analysis showed that awareness of the value and benefits of modern technology makes business management companies investigated systematically improve existing intra-system planning. Reviewed operational budgets, which are the source data for the compilation of the financial budget of the enterprise that includes a number of budgets - budget of revenues and operating expenses, which summarize the results of financial and economic activities of the period i show the effectiveness of managerial decisions; budget cash flow, which enables effective management of the solvency of the company; the budget balance, which shows the composition and value of the property, which is owned by the company, as well as sources of funds for the formation of this property. Budgeting is necessary for the further economic development of the company. In the first stage of budgeting – budget planning – important role played by the choice of appropriate methods of budgeting systems with the influence of factors as key to the formation of realistic, adequate and objective market-budgets in an organization. Productive activity budgeting system, which ensures efficient operation of the business depends on maximum detail budgets and their assessment by the relevant criterion.
Organization of the budgeting system on transport companies
Keywords: бюджетування; автотранспортні підприємства; витрати операційної діяльності; витрати на оплату праці; budgeting; automobile company; operating costs; labor costs; 658.012; 338.45